The Use of Visual Media in Christian Religious Education Instruction for Grade III Students at SD Negeri 1 Panarung, Palangka Raya - Helnita; Tirta Susila; Sri Gunarti Sabdaningrum (CV. Edujavare Publishing, 2026)
The Use of Visual Media in Christian Religious Education Instruction for Grade III Students at SD Negeri 1 Panarung, Palangka Raya